Evaluation of the multivalent immune protective effects of the Vibrio fluvialis outer membrane protein VF17320, and its DNA and IgY antibody vaccines in fish - Xiao, Huihui; Cui, Pan; Chen, Jing; Meng, Libing; Che, Xixian; Ma, Zijian; Wu, Xiaoqing; Lu, Juan; Sun, Shujun; Zhu, Guoping; Liu, Yong; Liu, Xiang (Frontiers in Veterinary Science, 2025)
IntroductionVaccines exhibit characteristics such as no residue, low drug resistance, and environmental friendliness, and demonstrate application value in aquaculture.Methods and resultsThe protein, DNA, and egg yolk antibody (IgY) vaccines targeting the Vibrio fluvialis outer membrane protein VF17320 were immunized to fish (Carassius auratus) and subsequently challenged with V. fluvialis and Aeromonas hydrophila. The results indicated that the three vaccines enhanced the expression levels of immune-related factors of acid phosphatase (ACP), alkaline phosphatase (AKP) and lysozyme (LZM) (p < 0.01), provided immune protection against bacterial infections (p < 0.01), effectively reduced kidney bacterial counts (p < 0.01), and increased the phagocytic activity of white blood cells in C. auratus (p < 0.01). Furthermore, the three vaccines downregulated the expression of inflammation-related genes (p < 0.01) and antioxidant-related factors (p < 0.01) to mitigate the inflammatory and antioxidant response in C. auratus, respectively. Histopathology revealed that the three vaccines preserved the integrity of visceral tissue, and immunofluorescence demonstrated that the vaccines reduced apoptosis and DNA damage in the kidney cells induced by bacterial infection.DiscussionOverall, the three vaccines exhibit the potential to combat various bacterial infections and can serve as multivalent vaccine candidates for aquaculture.